IDENTIFIKASI KERAGAMAN KHAMIR YANG DIISOLASI DARI TANAH KEBUN BIOLOGI WAMENA KABUPATEN JAYAWIJAYA, PROPINSI PAPUA - Kanti, Atit; Latupapua, H.J.D. (Perhimpunan Biologi Indonesia, 2001)
ABSTRACTThe Identification of Yeasts Which Were Isolated from Soils in the Wamena Biological Garden, Jayawijaya Residence, Papua Province. The present study deals with the isolation and identification of yeasts isolated from soil samples in The Wamena Biological Garden, Papua. Microbial population in 11 samples were estimated by plate count method. The yeasts population were ranged from 30.0 x102 until 16.5 x106 cells/g soil. Fifteen isolates of yeasts were taxonomically studied. On the basis of morphological and physiological characteristics these isolates were belonging to two group namely ascomycetous-imperfect yeasts and basidiomycetous yeasts. Futher, they were separated into three group. Out of 15 isolates, eleven isolates were included in group I and identified into genus level as Cryptococcus, three in group II as Candida and one isolate in group III identified into species level as Cryptococcus albidus. Type of sample sources appeared has no effect on yeasts diversity as shown by similar yeast isolate was observed isolated from different sources.Key words : Ascomycetous-imperfect yeasts, basidiomycetous yeasts, The Wamena Biological Garden, Papua.